Determination of Uranium by Spectrophotometric Method with Arsenazo III - Lazo, Pranvera; Cullaj, Alqi; Dogjani, Safet; Lubonja, Filip (Asian Journal of Chemistry, 2010)
Uranium is separated and preconcentrated from interfering elements by liquid extraction with 20% tributylphosphate (TBP) in benzene solution, prior to spectrophotometric determination with Arsenazo III in HCl medium (pH = 2.5), stabilized by buffer solution. Sodium fluoride and EDTA are used to complex calcium, rare earth elements (RE) and iron because they interfere in urani urn determination. The method is applicable in sediments and soil samples in the range of 0.25-10.0 μg of U/L. It should be used in water samples, too, in the range up to 0.25 μg of U/L for 20 to 50 mL of water sample.